2022
DOI: 10.3233/jbr-211554
|View full text |Cite
|
Sign up to set email alerts
|

Key genes for phenylpropanoid metabolite biosynthesis during half-highbush blueberry (Vaccinium angustifolium×Vaccinium corymbosum) fruit development

Abstract: BACKGROUND: Blueberry fruits contain large amounts of phenolic compounds derived from the phenylpropanoid pathway. Their biosynthesis is complex, involving many enzymes. OBJECTIVE: We sought to investigate the content of phenylpropanoid-derived compounds and identify key genes involved in the phenylpropanoid metabolite pathway during half-highbush blueberry fruit development. METHODS: Phenylpropanoid metabolite contents were determined by high-performance liquid chromatography (HPLC) and spectrophotometry. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…FLS encodes a key enzyme that catalyses the last steps in the formation of quercetin from phenylalanine (Li et al, 2020;Yang et al, 2022). In our study, we confirmed the expression levels of FLS by transcriptomics and fluorescent real-time quantitative PCR (qPCR), which showed that both quercetin and myricetin (which is synthesized from quercetin) metabolism were positively related to the expression of FLS (Figure 4c), and there were higher concentrations of myricetin and quercetin as well as higher expression of FLS in invasive populations of T. sebifera (Figure 4a,b).…”
Section: Discussionmentioning
confidence: 99%
“…FLS encodes a key enzyme that catalyses the last steps in the formation of quercetin from phenylalanine (Li et al, 2020;Yang et al, 2022). In our study, we confirmed the expression levels of FLS by transcriptomics and fluorescent real-time quantitative PCR (qPCR), which showed that both quercetin and myricetin (which is synthesized from quercetin) metabolism were positively related to the expression of FLS (Figure 4c), and there were higher concentrations of myricetin and quercetin as well as higher expression of FLS in invasive populations of T. sebifera (Figure 4a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin is a ubiquitous flavonoid in plants and the predominant flavanol in leaves of T. sebifera (Wang et al 2012;Tian et al 2021). FLS encodes a key enzyme that catalyzes the last steps in the formation of quercetin from phenylalanine (Li et al 2020;Yang et al 2022). In our study, we confirmed the expression levels of FLS by transcriptomics and fluorescent real-time quantitative PCR (qPCR), which showed that both quercetin and myricetin (which is synthesized from quercetin) metabolism were positively related to the expression of FLS (Figure 4c), and there were higher concentrations of myricetin and quercetin as well as higher expression of FLS in invasive populations of T. sebifera (Figure 4a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolite biosynthesis is largely regulated at the transcriptional level due to modified expression levels of genes (Yang et al 2022). However, the mechanistic basis of enhanced mutualism from evolved changes in gene expression is still not understood.…”
Section: Introductionmentioning
confidence: 99%
“…WGCNA has been widely used to identify gene regulatory networks from different KEGG pathways ( Zhu et al., 2019 ; Li et al., 2022 ). The biosynthesis of flavonoid compounds is co-regulated by multiple genes (e.g., PAL , 4CL , CHI , and FLS ) during half-high blueberry fruit development ( Yang et al., 2022b ). In the current study, we assembled the regulatory network of the phenylpropanoid biosynthesis pathway under UV radiation using WGCNA.…”
Section: Discussionmentioning
confidence: 99%